Isolamento e caracterização de células tronco mesenquimais derivadas de geléia de Wharton bovina e seu potencial para uso na clonagem por transferência nuclear - Da Silva, Carolina Gonzales; Martins, Carlos Frederico; Cardoso, Tereza Cristina [UNESP]; Da Cunha, Elisa Ribeiro; Bessler, Heidi Christina; McManus, Concepta Margaret; Pivato, Ivo; Báo, Sônia Nair (FapUNIFESP (SciELO), 2016)
Wharton’s jelly is a source of mesenchymal stem cells (MSCs) that had not yet been tested for bovine embryo production by nuclear transfer (NT). Thus, the objective of this study was to isolate, characterize and test MSCs derived from Wharton’s jelly for embryo and pregnancy production by NT in cattle. The umbilical cord was collected during calving and cells derived from Wharton’s jelly (WJCs) were isolated by explant and cultured in Dulbecco’s Modified Eagle Medium. Skin Fibroblasts (FB) were isolated after 6 months of life. Morphological analysis was performed by bright field and scanning electron microscopy (SEM) during cell culture. Phenotypic and genotypic characterization by flow cytometry, immunocytochemistry, RT-PCR and differentiation induction in cell lineages were performed for WJC. In the NT procedure, oocytes at the arrested metaphase II stage were enucleated using micromanipulators, fused with WJCs or FB and later activated artificially. SEM micrographs revealed that WJCs have variable shape under culture. Mesenchymal markers of MSCs (CD29+, CD73+, CD90+ and CD105+) were expressed in bovine-derived WJC cultures, as evidenced by flow cytometry, immunocytochemistry and RT-PCR. When induced, these cells differentiated into osteocytes, chondrocytes and adipocytes. After classification, the WJCs were used in NT. Blastocyst formation rate by NT with WJCs at day 7 was 25.80±0.03%, similar to blatocyst rate with NT using skin fibroblasts (19.00±0.07%). Pregnancies were obtained and showed that WJCs constitute a new cell type for use in animal cloning.
Isolation and characterization of mesenchymal stem cells derived from bovine Wharton’s jelly and their potential for use in cloning by nuclear transfer
Keywords: Cloning; Mesenchymal stem cell; Umbilical cord